Eksplorasi Etnomatematika Tradisi Meron di Desa Sukolilo Kecamatan Sukolilo Kabupaten Pati - Suci Damayanti; Nanang Nabhar Fakhri Auliya (Ar-Riyadhiyyat: Journal of Mathematics Education, 2023)
The aims of this study are 1) to describe the procession of carrying out the Meron tradition in Sukolilo Village, Sukolilo District, Pati Regency; 2) to explore the ethnomathematics concept contained in the meron tradition in Sukolilo Village, Sukolilo District, Pati Regency. This type of research is ethnographic research with a qualitative approach. Data collection is done by observation, interviews, and documentation. Data analysis was performed by data collection, data reduction, data presentation and verification. Checking the validity of the data is done by using, increasing persistence, triangulation and holding member checks. This research was conducted because there was no research on the Meron tradition which discussed its relationship with mathematics. Based on the results of the study it was found that 1) the Meron tradition procession in Sukolilo Village, Sukolilo District, Pati Regency was carried out in stages starting from the preparation stage, the procession implementation and post procession. In the preparatory stage consisting of forming committees, determining the time, events, and preparing various needs to be used in the Meron celebration ceremony, the implementation stage of the procession consists of the preliminary ceremony, Meron's departure and ends with a prayer together while the post-procession stage is carried out by parading again go to their respective homes. 2) The ethnomathematics obtained in this study are basic mathematical measurement concepts such as counting, measuring, and identifying. Counting activities are found when calculating the number of once of each meron, measuring activities are found when estimating the area and circumference of a meron, as well as the minimum distance for displaying meron while identifying activities are found in some basic geometric concepts that exist in meron such as angles, lines, plane shapes and geometry.